The Putty-Clay Perspective on the Capital-Energy Complementarity Debate - Struckmeyer, Charles S. (The Review of Economics and Statistics, 1987)
This paper argues that capital-energy complementarity is a short-run phenomenon reflecting the fixed ex post nature of factor employment in a putty-clay technology. When an empirical specification is employed that measures firms' ex ante choice of technique, capital and energy are found to be long-run substitutes. However, further analysis of the standard translog and putty-clay models with nonnested hypothesis tests reveals that neither specification is an adequate representation of technology. The results suggest that there is a dynamic adjustment process in the data that is not fully captured in either model. Copyright 1987 by MIT Press.